Effect of early continuously intravenous tranexamic acid on perioperative blood loss in thoracolumbar burst fractures with neurological symptoms. Issue 36 (9th September 2022) - Lu, Enhui; Huang, Tianji; Tan, Yun
Abstract : There is still a conflict between early surgical decompression and increased bleeding resulting from early surgery for thoracolumbar burst fractures (TBF) with neurological symptoms. The aim of this study is to investigate the effect of early continuously intravenous tranexamic acid (TXA) on perioperative blood loss in TBF with neurological symptoms who underwent early surgery. A retrospective comparative analysis was performed. The patients in study group were treated with intravenous TXA 15 mg/kg every 24 hours after admission besides intravenous TXA 15 mg/kg before skin incision and patients in control group were treated with intravenous TXA 15 mg/kg before skin incision only. Perioperative blood loss was compared between the 2 groups. The hemoglobin at admission, before surgery, 1 day and 3 days after surgery, the operation time, drainage time, blood transfusion and volume, incidence of complications and length of hospital stay were also compared. The operation time, preoperative, intraoperative, total, hidden amounts of blood loss in TXA group were significantly lower than those in control group ( P < .001). The hemoglobin level in the TXA group was significantly higher than that in the control group before and 1 day after surgery ( P < .05). The remove drainage time, hospitalization time, blood transfusion rate and volume in the TXA group were significantly lower than those in the control group ( P < .001). There was no significant difference in the incidence of lower limb thrombosis between the 2 groups ( P > .05). Early continuously intravenous TXA reduces the perioperative blood loss of patients with TBF who underwent early posterior fracture reduction, nerve decompression and pedicle screw fixation.